Clinical and molecular genetic analysis of cytologically uncertain thyroid nodules in patients with thyroid disease - Lukas, Jindrich; Hintnausova, Barbora; Sykorova, Vlasta; Syrucek, Martin; Maly, Marek; Lukas, David; Duskova, Jaroslava (Biomedical papers, 2025)
Background. The current requirement is to establish the preoperative diagnosis accurately as possible and to achieve an adequate extent of surgery. The aim of this study was to define the preoperative clinical and molecular genetic risks of malignancy in indeterminate thyroid nodules (Bethesda III and IV) and to determine their impact on the surgical strategy. Methods. Prospectively retrospective analysis of 287 patients provided the basis of preoperative laboratory examination, sonographic stratification of malignancy risks and cytological findings. Molecular tests focused on pathogenic variants of genes associated with thyroid oncogenesis in cytologically indeterminate nodules (Bethesda III and IV). The evaluation included clinical risk factors: positive family history, radiation exposure and growth in size and/or number of nodules. Results. Preoperative FNAB detected 52 cytologically indeterminate nodules (28.7%) out of 181 patients. Postoperative histopathological examination revealed malignancy in 12 cases (23.7%) and there was no significant difference between Bethesda III and IV categories (P=0.517). Clinical risk factors for malignancy were found in 32 patients (61.5%) and the presence of at least one of them resulted in a clearly higher incidence of malignancy than their absence (31.3% vs. 10.0%, respectively). Pathogenic variants of genes were detected in 12/49 patients in Bethesda III and IV, and in 4 cases (33.3%) thyroid carcinoma was revealed. The rate of malignancies was substantially higher in patients with pathogenic variants than in those without (33.3% vs. 16.2%, respectively). Conclusions. Our experience implies that molecular genetic testing is one of several decision factors. We will continue to monitor and enlarge our patient cohort to obtain long-term follow-up data.
Keywords: thyroid nodules; cytology; molecular testing; thyroidectomy